Standardization Eﬀorts for Ayam Goreng Kalasan Industry Cluster Through a Partnership Between the University and Local Government to Maintain its Local Wisdom - Sukartiko, Anggoro Cahyo; Supartono, Wahyu; Zaidir, Zaidir; Neisyafitri, Rendayu Jonda; Setiyono, Rahmat (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2024)
A community service partnership is carried out between a university and a local government to standardize processes and products produced by the Ayam Goreng Kalasan industry cluster. Eﬀorts are made through a series of focused discussion activities, knowledge sharing, and material provision, as well as training and mentoring on aspects of standardization, product diversiﬁcation,and promotion toward marketing with a broader scope. The ﬁrst three stages were carried out with the involvement of local government. The results of the community service implementation were measured using a comparison of knowledge of business actors before and after the implementation of the activities. A total of 31 business actors, as members of the Ayam Goreng Kalasan Maju Makmur industry cluster, have participated in this activity. Increased knowledge is observed in all aspects: standardization, diversiﬁcation, management, and marketing. The collaboration between the university and the local government, therefore, can increase the participation of business actors, accelerate the required standardization and certiﬁcation process, and further increase the possibility of sustainability of cluster business development.